Public and Private Institutional Impact Related to Efficient Administration of Environmental Factors. A Comparative Study at European Level - Borza, Mioara; Badivuku-Pantina, Myrvete (Wydawnictwo Uniwersytetu Rzeszowskiego, 2012)
The new status of some European countries, obtained by adhesion to the European Union, has produced a series of essential changes, reflected on typology of economic activities and institutional framework for their deployment. In this paper we will realize a comparative analysis, based on statistical data, related to the administration of environmental factors in economic units, public and private, for two countries with different European status: Romania – newly member of the European Union and Kosovo – that is not member of the European Union. The aim of this paper is to highlight the differences caused by institutional framework related to environmental factors administration and their effects for the efficiency of administration. The comparison will be realized for a set of public and private institutions from Romania and Kosovo. The present study starts from some premises and notices about the differences from entrepreneurial administration. So, we observed the major changes caused by privatization of public institutions, but without general benefices for national economy. For this paper we selected the changes directly connected with environmental factors. Thus, we noted: in forestry, the retrocession of forest is affected by an inefficient administration; by agrarian reform, the agricultural land were returned, and now, after 20 years, the agriculture has become one of subsistence; a lot of agricultural areas were transformed, by private investors, in land with real estate destinations; although we got the financial supports in the pre-accession period (SAPARD funds), the investment in administration and protection of environment protection weren’t a priority. In final of the paper, based on the elaborated conclusions, we will formulate a set of proposals about the efficiency of environmental factors administration, with hope that the institutional experience of a country member of the EU will be a model for institutions from countries that is not yet EU member. The main proposal will focus on public-private partnerships.

Nowa sytuacja niektórych państw europejskich, wynikająca z akcesji do Unii Europejskiej wytworzyła szereg istotnych zmian odzwierciedlonych w typologii działalności gospodarczej i instytucjonalnych ramach jej rozwoju W opracowaniu dokonuje się porównawczej analizy, opartej na danych statystycznych, odnoszącej się do zarządzania czynnikami środowiskowymi w jednostkach gospodarczych publicznych i prywatnych, dla dwóch państw z odmiennym statusem europejskim: Rumunii – nowego członka Unii Europejskiej oraz Kosowa, które nie jest członkiem Unii Europejskiej. Celem opracowania jest ukazanie różnic mających swoje przyczyny w otoczeniu instytucjonalnym, odnoszących się do zarządzania czynnikami środowiskowymi i ich znaczenia dla efektywności administrowania. Porównania dotyczą zestawu publicznych i prywatnych instytucji z Rumunii i Kosowa. Opracowanie rozpoczynają uwagi odnośnie do różnic w zarządzaniu przedsiębiorczym. Obserwowane są istotne zmiany następujące w wyniku prywatyzacji instytucji publicznych, które jednak nie przynoszą ogólnych korzyści gospodarce narodowej. Dla celów niniejszego opracowania zostały przeanalizowane zmiany bezpośrednio związane z czynnikami środowiskowymi. Zaobserwowano w tym zakresie: w leśnictwie: wpływ nieefektywnej administracji na proces zwrotu terenów leśnych; w reformie rolnej: ziemia rolnicza została zwrócona i obecnie, po 20 latach, rolnictwo stanowi jedno ze źródeł utrzymania zapewniających przetrwanie; liczne obszary rolnicze zostały przekształcone przez prywatnych inwestorów w działki budowlane; pomimo finansowego wsparcia w okresie przedakcesyjnym (fundusze SAPARD) inwestycje w administrowanie i ochronę środowiska nie były priorytetem. W końcowej części opracowania, opartej na wypracowanych wnioskach, został sformułowany zestaw propozycji dotyczących efektywności administrowania czynnikami środowiskowymi, z nadzieją, że instytucjonalne doświadczenia kraju członkowskiego UE będą stanowiły model instytucjonalny dla państw niebędących członkami ugrupowania. Główna propozycja dotyczy partnerstwa publiczno-prywatnego.